2014
DOI: 10.1088/1674-1056/23/4/049201
|View full text |Cite
|
Sign up to set email alerts
|

Early warning signals of abrupt temperature change in different regions of China over the past 50 years

Abstract: Early warning signals of abrupt temperature change in different regions of China over the past 50 years * Tong Ji-Long(仝纪龙) a) , Wu Hao(吴 浩) a)b) † , Hou Wei(侯 威) c) , He Wen-Ping(何文平) c) , and Zhou Jie(周 杰) b) a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The PDO has been considered as an important indicator of the decadal variability of the Pacific Ocean (Meehl et al, 1993), which has a strong relationship with the climate of China (Wang et al, 2013). It has been shown in many previous studies, that this index has experienced several abrupt changes over the past 100 years (Mantua et al, 1997;Tsonis et al, 2007), and that all of these abrupt changes correspond to the global climate changes.…”
Section: Characteristics Of Abrupt Change Process Of Pacific Decadal Oscillationmentioning
confidence: 99%
See 1 more Smart Citation
“…The PDO has been considered as an important indicator of the decadal variability of the Pacific Ocean (Meehl et al, 1993), which has a strong relationship with the climate of China (Wang et al, 2013). It has been shown in many previous studies, that this index has experienced several abrupt changes over the past 100 years (Mantua et al, 1997;Tsonis et al, 2007), and that all of these abrupt changes correspond to the global climate changes.…”
Section: Characteristics Of Abrupt Change Process Of Pacific Decadal Oscillationmentioning
confidence: 99%
“…The climate system is complex and chaotic (Shi, 2009). The abrupt climate change is described as the system transitioning from one stable state to another (Thom, 1972;Tong et al, 2014), i.e., the system swings between different states (Lorenz, 1976;Charney and DeVore, 1979), and it also has been verified in the climate system (Dai et al, 2012;Baker and Charlson, 1990;Wang et al, 2012;Alley et al, 2003;Xiao et al, 2011). Detection methods (Wan and Zhang, 2008;Fu and Wang, 1992;Yamamoto et al, 1986) have been greatly developed.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the critical slowing down theory, Yan et al [40] processed the data of radon concentrations in water and revealed that the early-warning signals of increasing variances and autocorrelation coefficients appeared before the Wenchuan earthquake in 2008. In recent years, several scholars [41][42][43][44][45] applied this theory to climate data, such as the regional temperature in China, the Pacific Decadal Oscillation index and the intensity of Aleutian low, aiming to study the earlywarning signals of abrupt climatic changes. On the basis of existing early-warning signals, He et al [46][47][48] made some improvements and developed a set of quantitative earlywarning signals and methods for abrupt climatic changes.…”
Section: Introductionmentioning
confidence: 99%
“…The abrupt climate change is described as the system transitioning from one stable state to another (Thom, 1972;Tong et al, 2014), i.e., the system swings between different states (Lorenz, 1976;Charney and DeVore, 1979), and it also has been verified in the climate system (Dai et al, 2012;Baker and Charlson, 1990;Wang et al, 2012;Alley et al, 2003;Xiao et al, 2011). Detection methods (Wan and Zhang, 2008;Fu and Wang, 1992;Yamamoto et al, 1986) have been greatly developed.…”
Section: Introductionmentioning
confidence: 99%